Enhancing Extended Reality(XR) by using mobile devices emphasizing universal usage - Ahmed, Saadman; Kingshuk, Asif Fahad; Rabbi, Seyam; Hasan, Zaid Ibne; Nishi, Sayma Shultana (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.